Hiv Governance Through Law: Achievements And Challenges Of China's Legal Environment - Jinmei , Meng (Penerbit Universiti Sains Malaysia (USM Press), 2012)
Over the last two decades, the law relating to HIV in the People's Republic of China (PRC) has transitioned from denial towards positive responses to HIV. In the 1980–90s, the law provided for mandatory HIV testing and quarantine of people living with HIV/AIDS (PLWHA). It also banned HIV positive foreigners from entering or living in China. However, these defensive laws were ineffective in keeping HIV out of China and containing domestic HIV spread. In the mid- 1990s, the number of HIV infections sharply increased with more and more commercial blood donors being found to be infected with HIV. In the late 1990s, the government began to learn how to develop and implement effective HIV strategies and initiated pilot behavioural intervention programs such as condom promotion for sex workers and clean needle exchange for injecting drug users (IDUs). In 2004, China abandoned mandatory HIV testing and HIV quarantine. In 2006, the country legalised behavoural interventions. The ban on the immigration of HIV positive foreigners into China was lifted in 2010. However, China still has a long way to go before achieving good HIV governance by law. The anti-prostitution and anti-drug laws impede behavioural interventions. The laws against sex work and drug use and parts of HIV policy do not conform to international human rights standards. The weak anti-discrimination legal mechanism fails to prohibit HIV-based discrimination. There is a lack of an enabling legal environment for full community participation in all phases of HIV responses. In addition, the state secrets law creates barriers to promoting government transparency and accountability in the area of HIV.